Monogenic Diabetes in Overweight and Obese Youth Diagnosed with Type 2 Diabetes: The TODAY Clinical Trial - Kleinberger, Jeffrey W. (Genet Med, 2017)
PURPOSE: Monogenic diabetes accounts for 1–2% of diabetes cases. It is often undiagnosed, which may lead to inappropriate treatment. This study was performed to estimate the prevalence of monogenic diabetes in a cohort of overweight/obese adolescents diagnosed with type 2 diabetes (T2D). METHODS: Sequencing using a custom monogenic diabetes gene panel was performed on a racially/ethnically diverse cohort of 488 overweight/obese adolescents with T2D in the TODAY clinical trial. Associations between having a monogenic diabetes variant and clinical characteristics and time to treatment failure were analyzed. RESULTS: Over four percent (22/488) had genetic variants causing monogenic diabetes (7 GCK, 7 HNF4A, 5 HNF1A, 2 INS, and 1 KLF11). Patients with monogenic diabetes had a statistically, but not clinically, significant lower BMI Z-score, lower fasting insulin, and higher fasting glucose. Most (6/7) patients with HNF4A variants rapidly failed TODAY treatment across study arms (HR=5.03, p=0.0002), while none with GCK variants failed treatment. CONCLUSIONS: Discovery of 4.5% of patients with monogenic diabetes in an overweight/obese cohort of children and adolescents with T2D suggests monogenic diabetes diagnosis should be considered in children and adolescents without diabetes-associated autoantibodies and maintained C-peptide, regardless of BMI, as it may direct appropriate clinical management.